Global Embedding of the Reissner-Nordström Metric in the Flat Ambient Space - Paston, S.A.; Sheykin, A.A. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
We study isometric embeddings of non-extremal Reissner-Nordström metric describing a charged black hole. We obtain three new embeddings in the flat ambient space with minimal possible dimension. These embeddings are global, i.e. corresponding surfaces are smooth at all values of radius, including horizons. Each of the given embeddings covers one instance of the regions outside the horizon, one instance between the horizons and one instance inside the internal horizon. The lines of time for these embeddings turn out to be more complicated than circles or hyperbolas.